Role of stress in progression of Migraine - Noushad , Shamoon; Ahmed , Sadaf; Khalid, Huma; Naseer, Rida; Tunio, Ikram; Shaikh Tahir (International Journal of Endorsing Health Science Research, 2014)
The mental and physiological stresses can be an important trigger of migraines & headaches. These strains act to enhance the progression of migraine that could be psychological, physiological stress, Environmental stress or Chemical stress. The population data of 185 people have taken which include the ages from 14-60 years. The data were analyzed by ICHD-II criteria .The duration of the research was from-February 2012 to December 2012.The targeted population were of both genders age ranges 18-25 years. The data have collected in two parts, before examination and during examination. The obtain result shows that the frequency of migraine is higher in women as compare to men. Mostly people were suffering from mild psychological stress that might be periodical stress as approximately 50% people were students who were under examination stress as the exams were about to held. Nutritional stress is another major factor as the high temperature causes dehydration resulted in vasoconstriction resulted in sensation of pain. Environmental stress was an additional cause for students. Physiological stress was also noticed as the main cause that bring about the initiation of migraines period whether it could also leads towards the Menstrual migraine that has a sign of vomiting or nausea. Individual concerns with healthy life patterns and stress free conditions could help a person to reduce or prevent the migraine.